The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/horticulturae9101071
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Metabolite and Transcriptome Sequencing Analysis Reveals White Flowers in Rhododendron dauricum var. albiflorum

Huaizhi Mu,
Xuhong Jin,
Yue Zhang
et al.

Abstract: Rhododendron dauricum is a cold-hardy shrub integrating ornamental, medicinal, and aromatic functions. Flower color is an important feature related to ornamental value for breeders and consumers. Nevertheless, the coloration mechanism of flower color in R. dauricum is still unclear. R. dauricum var. albiflorum is a white flower variety of R. dauricum. In this study, an integrative analysis of the metabolome and transcriptome was conducted between R. dauricum var. albiflorum and R. dauricum. A total of nine ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…In a study of the wild type of primrose (yellow petals) and its variants (yellow transformed to red), it was found that the orange and red primrose types contain anthocyanins such as cyanidin-3-O-glucoside [23]. Most of the current research on rhododendrons focuses on white rhododendrons and red rhododendrons, and many studies on white rhododendrons have shown that white rhododendrons have lower anthocyanin contents [22,24,25]. Additionally, the enzyme genes CHS, F3 ′ 5 ′ H, FLS, I2 ′ H, HID, DFR, and LAR may have a role in the alteration of petal colour in R. liliiflorum [21,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of the wild type of primrose (yellow petals) and its variants (yellow transformed to red), it was found that the orange and red primrose types contain anthocyanins such as cyanidin-3-O-glucoside [23]. Most of the current research on rhododendrons focuses on white rhododendrons and red rhododendrons, and many studies on white rhododendrons have shown that white rhododendrons have lower anthocyanin contents [22,24,25]. Additionally, the enzyme genes CHS, F3 ′ 5 ′ H, FLS, I2 ′ H, HID, DFR, and LAR may have a role in the alteration of petal colour in R. liliiflorum [21,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is widely used in research on plant colour formation [25,29,30]. Metabolic group studies have studied four noncolours of wheat, explaining that the reason for the colour difference of wheat is potentially the accumulation of flavonoid compounds [31].…”
Section: Introductionmentioning
confidence: 99%